The role of Anglo-Saxon great hall complexes in kingdom formation, in comparison and in context AD 500-750 - McBride, Adam, 1989- (Archaeopress Archaeology, 2020)
Examining the role of great hall complexes in kingdom formation through an expansive and ambitious study, this text incorporates new fieldwork, new quantitative methodologies and new theoretical models for the emergence of high-status settlements and the formation and consolidation of supra-regional socio-political units.